PENINGKATAN PENGETAHUAN IBU TENTANG IMUNISASI DPT-HB-HIB LANJUTAN PADA BADUTA DI MASA PANDEMI COVID-19 SETELAH PEMBERIAN PENYULUHAN KESEHATAN PENINGKATAN PENGETAHUAN IBU TENTANG IMUNISASI DPT-HB-HIB LANJUTAN PADA BADUTA DI MASA PANDEMI COVID-19 SETELAH PEMBERIAN PENYULUHAN KESEHATAN - Sondang Deri Maulina Pasaribu; Rizky Fitria Kartikasari; Vera Nurul Novalinda (Jurnal Kesehatan STIKes IMC Bintaro, 2022)
Introduction immunization is one of the effective prevention efforts for the community in providing specific immunity to diseases that can be prevented by immunization. It is important for the mother to understand what DPT-HB-HIB immunization is and its time so that it can be given according to a predetermined schedule. The problem that arises is that many parents are worried about doing immunization services during the COVID-19 pandemic. The purpose of this study was to determine the effect of health education on the level of knowledge of the mother about advanced DPT-HB-HIB immunization in 2 years old children during the COVID-19 pandemic in Anggrek integrated service centers in Pondok Betung in 2021. The research method used is quantitative with a research design of One Group Pretest Posttest Design. The sampling technique used was Quota Sampling with a total of 22 respondents. In this study, the data analysis used is Paired Sample T-Test (p<0,05). The results is known that from 22 respondents before health education about advanced DPT-HB-HIB immunization there were 12 (54.6%) respondents who had sufficient knowledge levels and after the health education was conducted, there were 19 (86.4%) respondents who had a good level of knowledge. The p value is 0.000<0.05. The conclusion in this study is that there is an effect of providing health education on the level of knowledge of the mother about advanced DPT-HB- HIB immunization in 2 years old children during the COVID-19 pandemic in Anggrek integrated service centers in Pondok Betung in 2021.